Performance analysis of broadband self-interference cancellation at RF domain in co-frequency co-time full duplex systems - Jun WANG; Hong-zhi ZHAO; Wan-zhi MA; You-xi TANG; Chao-jin QING (Tongxin xuebao)
Due to the lack of performance analysis of the RF domain broadband self-interference cancellation algorithms in the co-time and co-frequency full duplex system,the multi-tap RF domain self-interference cancellation structure were considered,and the optimal solutions of its parameters to minimize the residual interference signal power were discussed,then its achievable interference cancellation capability was analyzed.By analysis and simulation,the performance of the multi-tap structure was associated with the interference bandwidth,the carrier frequency,and the differences between the multi-tap delays and multipath delays of the self-interference channel.The greater the signal bandwidth is,or the larger the differences between the multi-tap delays and multipath delays are,the worse the interference cancellation performance is.Besides,the interference cancellation performance is periodic oscillation with the increase of carrier frequency.